Application of Multiplication Method for Developing Tourism Students’ Speaking Skills - A Lumettu; T Lusje Runtuwene (KnE Social Sciences, 2019)
Poor English skills partly result from limited practice. English teaching requires a method which provides enough time for speaking practice. In this research, Multiplication Method was used in developing students’ speaking ability where 12 students were trained to be trainers for their 36 juniors. Thus it started from one teacher who trained 12 students and later these 12 students trained 36 students. By the end of the second semester, there were 48 students who could speak English resulting from this program compared to only 5 or 6 by using normal teaching. The analysis method was qualitative method supported by quantitative data. The method and instrument of research were guided interview, systematic observation and documentation. The results of the research show that the pretest average grade of the experimental group was 64 and that of the control group was 65. After this program, the post- test average grade significantly increased to 98 while that of the control group only rose to 76. The conclusion is that the application of multiplication method is very effective in improving students’ speaking ability while multiplying the number of students who can speak English.  Keywords: Application, Multiplication Method,Developing, Tourism, Speaking Skills.